The geochemistry of Au–Ag minerals and base‐metal sulphides as indicators for gold precipitation: Case study of the Shihu gold deposit, central North China Craton. (25th July 2019) - Zeng, Yong‐Jie; Li, Lin; Li, Sheng‐Rong; Santosh, M.; Alam, Masroor
Abstract : The Shihu quartz vein‐type gold deposit, the largest gold deposit in the central North China Craton, occurs within wall rocks of Neoarchean TTG (tonalite–trondhjemite–granodiorite) gneiss and shows a close relationship with the early Cretaceous Mapeng granitoid pluton and various intermediate–mafic dykes. The occurrence, morphology, composition, and precipitation mechanism of the Au–Ag minerals are short of research, which is the purpose of this study. The primary mineral assemblage of orebody contains quartz, calcite, and base‐metal sulphides including pyrite, galena, sphalerite, chalcopyrite, and minor pyrrhotite and enargite. The Au–Ag minerals can be classified into three distinct types, namely, (a) quartz‐hosted, (b) pyrite‐hosted, and (c) base‐metal sulphidehosted, corresponding to formation sequence. Electron microprobe analysis indicates that these Au–Ag minerals show fineness (=Au/[Au + Ag] × 1, 000) ranging from 976 to 366 with an average of 667 and are rich in Bi, Te, and Hg while deficient of Cu, As, and Se. Bismuth and tellurium in the Au–Ag minerals show a linear relationship with Au, whereas in the coexisted sulphides are almost below detection limits. We suggest that Bi and Te fundamentally influenced the transportation, enrichment, and precipitation of gold as scavengers to concentrate and deposit gold at the location with an "appropriate distance" from magma. Phase analyses of native bismuth and Bi–Te minerals included in pyrite, reported for the first time in Shihu Gold deposit, imply that the gold precipitation witnessed the ore‐forming fluid evolution with log f Te2 decreasing from approximately −11 to approximately −15 and log f S2 increasing from approximately −13 to more than −11. Mineralogical mapping with the fineness of Au–Ag minerals (fineness contours) suggest that the ore‐forming fluids came from the deep earth beneath the north of the mining area with excellent gold potential, which has been verified by later drilling.